Study guides

Q: What is 2 minus n minus 7n?

Write your answer...

Submit

Related questions

7n(n−1)

n > 2

It is 2n^3 + 7n^2 - 13n + 3

n*(9 - 2) = 2*7 = 7n

8n + 7 - n - 98 = 7n - 91

7n + 1 = 6n + 8 7n=6n+7 (minus 1 from each side) n=7 (7n-6n equals n, you are left with n=7)

-2n - 4p + 2. Without knowing n and p, that's the best you get.

4n - 7n = 21(4-7) n =21-3n = 21divide both sides by -3n = -7

t(n) = 5 - 7n for n = 1, 2, 3, ... The difference between each term is -7, therefore the nth term will be: t(n) = -2 + -7 × (n - 1) = -2 + 7n + 7 = 5 - 7n

1 - 7n = 15 - 5n Add 5n to each side: 1 - 7n + 5n = 15 -5n + 5n ie 1 - 2n = 15; subtract 1 from each side: -2n = 14 divide both sides by -2: n = -7

9n-2=7n+50 7n+9n=50+2 16n=52 n= 3.25

-7n2 + 74n + 33 = -7n2 + 77n - 3n + 33 = -7n*(n - 11) - 3*(n - 11) = =(-7n - 3)*(n - 11) = -(7n +3)*(n - 11)

n(2n - 1)(2n + 7)

2 - 7n = 6therefore 7n = 2 - 6 = -4 and so n = -4/7 Then 5m + 7n = 6.4 becomes 5m - 4 = 6.4 so that 5m = 10.4 and then m = 10.4/5 = 2.08

Assuming you meant 7n (not just 7 at the end of your question) - first... simplify the equation. Numbers raised to powers get priority - so your new sum is... 5n - 64n + 25n + n + 7n.... This simplifies to... -26n

7n-45n=2 -38n=2 38n=-2 n=-2/38=-1/19

3n2 - 7n = 0 n(3n - 7) = 0 So either n = 0 or 3n-7 = 0 ie, either n = 0 or n = 7/3 = 21/3 = 2.33...

-7n - 8 + 6 = 13 - 2 Add 2 to each side: -7n - 8 + 6 + 2 = 13 simplify: -7n = 13 n = -13/7 = -16/7

10n + 3 = 7n + 53n = 2n = 2/3

n(7n-3) = 0 n = 0 or n = 3/7

38.The position to value rule is Un= (n2+ 7n - 2)/2 where n = 1, 2, 3, ...38.The position to value rule is Un= (n2+ 7n - 2)/2 where n = 1, 2, 3, ...38.The position to value rule is Un= (n2+ 7n - 2)/2 where n = 1, 2, 3, ...38.The position to value rule is Un= (n2+ 7n - 2)/2 where n = 1, 2, 3, ...

n = 3/2, n = 2

7n = 91n = 91÷7n = 13

Yes, and here's the proof: Let's start out with the basic inequality 4 < 7 < 9. Now, we'll take the square root of this inequality: 2 < √7 < 3. If you subtract all numbers by 2, you get: 0 < √7 - 2 < 1. If √7 is rational, then it can be expressed as a fraction of two integers, m/n. This next part is the only remotely tricky part of this proof, so pay attention. We're going to assume that m/n is in its most reduced form; i.e., that the value for n is the smallest it can be and still be able to represent √7. Therefore, √7n must be an integer, and n must be the smallest multiple of √7 to make this true. If you don't understand this part, read it again, because this is the heart of the proof. Now, we're going to multiply √7n by (√7 - 2). This gives 7n - 2√7n. Well, 7n is an integer, and, as we explained above, √7n is also an integer; therefore, 7n - 2√7n is an integer as well. We're going to rearrange this expression to (√7n - 2n)√7, and then set the term (√7n - 2n) equal to p, for simplicity. This gives us the expression √7p, which is equal to 7n - 2√7n, and is an integer. Remember, from above, that 0 < √7 - 2 < 1. If we multiply this inequality by n, we get 0 < √7n - 2n < n, or, from what we defined above, 0 < p < n. This means that p < n and thus √7p < √7n. We've already determined that both √7p and √7n are integers, but recall that we said n was the smallest multiple of √7 to yield an integer value. Thus, √7p < √7n is a contradiction; therefore √7 can't be rational, and so must be irrational. Q.E.D.

Simplifying 7n + 3 = 0 Reorder the terms: 3 + 7n = 0 Solving 3 + 7n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 7n = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 7n = 0 + -3 7n = 0 + -3 Combine like terms: 0 + -3 = -3 7n = -3 Divide each side by '7'. n = -0.4285714286 Simplifying n = -0.4285714286 or n = -3/7

People also asked